Paul Ehrlich: From magic bullets to chemotherapy. (Colombia Medica, 2008)
Paul Ehrlich is one of the most notable figures in the world of science. Considered by many as the father of chemotherapy, he was awarded the Nobel Prize in Physiology and Medicine in 1908 for his contributions to immunology. This document outlines some of his most important findings, including those who led him to create his famous «magic bullets», precursors of current chemotherapeutic agents.